2018
DOI: 10.1108/apjml-01-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Sales technology usage

Abstract: Purpose The purpose of this paper is to model the key influencers or predictors for usage of technology by sales professionals in India. Design/methodology/approach This study examines the effect of individual, organizational and social factors on the use of technology. The method used for primary research is survey, and data have been collected from 556 sales professionals from across four industries in India. The empirical analysis consists of confirmatory factor analysis using structural equation modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…The perceived usefulness in this study has no effect on attitudes in the use of information technology-based accounting information systems. This result does not support hypothesis 2 and previous study by Rangarajan et al (2005), Robinson et al, (2005), and Upadhyay et al (2018) who concluded that perceived usefulness has positive effect on attitude. Perceived usefulness emphasizes the benefits of a system or technology.…”
Section: Perceived Usefulness On Attitudecontrasting
confidence: 99%
See 1 more Smart Citation
“…The perceived usefulness in this study has no effect on attitudes in the use of information technology-based accounting information systems. This result does not support hypothesis 2 and previous study by Rangarajan et al (2005), Robinson et al, (2005), and Upadhyay et al (2018) who concluded that perceived usefulness has positive effect on attitude. Perceived usefulness emphasizes the benefits of a system or technology.…”
Section: Perceived Usefulness On Attitudecontrasting
confidence: 99%
“…Previous research by Rangarajan et al (2005) and Robinson et al, (2005) show that salespeople who believe that particular technology will enhance their productivity in their jobs, they are more likely to have a more positive attitude toward the technology. Research by Upadhyay et al (2018) shows the same result that perceived usefulness has positive effect on attitude.…”
Section: Research and Hypothesis Developmentmentioning
confidence: 55%
“…Via a researcher's connections with five manufacturing companies, we were further connected to other companies. This sampling technique was used due to the lack of availability of the sampling frame, which is a vital requirement for probability sampling approaches ( Upadhyay, Khandelwal, Nandan, & Mishra, 2018 ). Snowballing entails the use of some members of the group of interest to approach other members ( Yadav, Dokania, & Pathak, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…This technique also helps enhance the chance of reaching not only industrial sectors but also individuals in industrial companies and target groups such as salespeople ( Yadav et al, 2016 ). Snowballing has been used to approach salespeople in prior studies ( Kooli, Tzempelikos, Foroudi, & Mazahreh, 2019 ; Nanarpuzha & Noronha, 2016 ; Upadhyay et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…These industries have also been actively adopting and operating BT to optimize the supply chain process and make transactions safer, more transparent, traceable and efficient (Queiroz and Wamba, 2019). Upadhyay Ashwani et al (2018) also suggested that it is important to examine the key influencers for organizational technology usage in which adoption of new technologies needs to be promoted throughout organizational individuals. Thus, a BT study can provide these industries with useful information for various aspects related to transforming, remodeling and leveraging their operations.…”
Section: Methodsmentioning
confidence: 99%